Bion's legacy to groups : selected contributions from the International Centennial Conference on the Work of W.R. Bion : Turin, July 1997 /: selected contributions from the International Centennial Conference on the Work of W.R. Bion : Turin, July 1997. (1998) - Unknown
No abstract available